Event recording in a clinical trial of a new medicine. Issue 6223 (3rd May 1980) - Simpson, R J; Tiplady, B; Skegg, D C
Abstract : In a double-blind trial of the effect of zimelidine on weight and appetite 24 obese patients were allocated at random to receive either zimelidine or placebo for eight weeks followed by the alternative treatment for eight weeks. Possible adverse effects were elicited by asking patients at weekly intervals whether they had experienced any symptoms or ailments and recording all such "events" on a special form. A conventional checklist of symptoms was also used. Among 19 patients who completed the trial the two methods of recording yielded similar patterns of events. Of symptoms not on the checklist, insomnia was more common during treatment with zimelidine. Event recording was found to be a practicable and convenient method of detecting possible adverse effects.